Pengelolaan Administrasi Kurikulum Sistem BDR (Belajar Dari Rumah) masa Pendemi Covid 19 di SMPN 2 Kepung Keling Kepung Kediri Tahun Ajaran 2020/2021 - Khoirotul Izzah; Hilatul Munawaroh (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
The curriculum is a system that has components that are closely related and support one another. The curriculum components consist of objectives, learning materials, methods, and evaluation. In this system form the curriculum will run towards an educational goal with mutual cooperation among all its subsystems. If one of the curriculum variables does not function properly, the curriculum system will run less well and optimally. Departing from the form of the curriculum, in the implementation of the curriculum, an organization of all its components is needed. In this organizing process, it will be closely related to planning, organizing, implementing, and controlling. Whereas management is one of the disciplines whose implications are implementing these processes. So in implementing curriculum implementation, a person who manages an educational institution must master the science of management, both to take care of education or the curriculum. Curriculum management is a pattern of empowering education personnel and other educational resources to improve the quality of education. The curriculum itself determines the success of teaching and learning activities maximally. Curriculum management deals with the management of learning experiences that require certain strategies to produce learning productivity for students. Especially during the current covid pandemic. Principals, teachers, and other staff members must be able to initiate and create a strategy where the implementation of the KMB continues even though it is constrained by this covid, which results in one of which is the absence of direct meetings or face-to-face meetings with students.